Preparation and characterization of mucoadhesive tablets of amoxicillin using natural and synthetic polymers - Goswami, D. S.; Sharma, M. (Journal of Applied Pharmaceutical Research, 2013)
Purpose of this research was to study mucoadhesive tablets of Amoxicillin trihydrate using Neem gum as mucoadhesive natural polymer. The conventional oral dosage form of this drug has low half life and high dosing frequency. Plant gums and mucilages are being used due to their abundance in nature, safety and economy. So in The present investigation was an effort to study the suitability of gum obtained from Azadirachta indica as mucoadhesive polymer. The present study aims to reduce the dosing frequency by using single and combinations of synthetic and natural polymers for preparation of mucoadhesive tablets. Various approaches to combine synthetic (HPMC K4M, carbopol 934P and sodium alginate) and natural (neem gum) polymers have been made to prepare total ten formulations. Further, different evaluation studies like friability, content uniformity, surface pH, wash-off and dissolution tests was done for all formulations. Results for in vitro drug release and wash-off studies suggest that the formulation (F1) containing neem gum has shown better mucoadhesive property. Other studies have shown satisfactory results in all ten formulations. Thus, the present investigation suggests that neem gum is suitable for preparation of mucoadhesive tablets